Social Well-Being Elements Through the Lens of Low-Income Group among Malays in Malaysia After 14th General Election: A Systematic Literature Review - Syamimi Waznah Hamdon,; Harliana Halim, (Journal of Technology Management and Business, 2022)
Social well-being is a condition where a community feels safe and comfortable living their lives without any constraints from anyone. Hence, it is vital to discover the main elements contributing to a community's social well-being in a multi-ethnic country. It will become the main guideline of how they want to be treated and helped. This systematic review aims to discover the social well-being elements through the lens of the Malay low-income group in Malaysia after 14th general election. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, thirteen related studies were identified from the Web of Science, Scopus databases and snowballing technique of related sources. Further review of the articles through qualitative analysis resulted in eight core themes on social well-being elements of Malay low-income group after GE-14, namely housing, religion, ethnic composure, health, management, environment, income, and education. These findings contribute to the enhancement of the field of social well-being, especially in a multi-ethnic democratic nation. Keywords: Social well-being, Malaysia 14th general election, low-income, Malays, systematic literature review.